Nilai-Nilai Sosial Dan Budaya Dalam Babad Tanah Jawi Terjemahan W.L. Olthof Serta Implikasinya Dalam Pembelajaran Sastra Di SMA: Sebuah Kajian Semiotik - Fifi Nofiyanti (UHAMKA Graduate School Thesis Abstract Collection, 2016)
This study seeks to preserve the classic literature that shaped the history of the story Babad Tanah Jawi. The story associated with teaching literature in high school, so that students, teachers, readers and the public remain to recognize and preserve the Babad Tanah Jawi. The story contains ancestral values therein, tells the story of the royal triumph in the island of Java in terms of social and cultural. Methodology This study uses qualitative descriptive method with content analysis techniques and Roland Barthes semiotic approach. Social values assessed value is social associative divided into: cooperation, accommodation and assimilation. The social value disassociative divided into: competition, conflict and controversy. While the value of the culture being studied is divided into seven components: language, knowledge systems, social organization, equipment and technology life, livelihood, as religion, and the arts. Semiotic theory used by Roland Barthes which divides semiotic meaning by denotation and connotation. The results of this study as a whole that is the social value associative divided into: cooperation 43 citations, 15 citations accommodation and assimilation 40 citations. The social value disassociative divided into: competition 10 citations, 12 citations contention and controversy 12 citations. While the value of the culture being studied is divided into seven components: language 27 citations, 31 citations knowledge systems, social organizations 88 citations, live equipment and technology 31 citations, 19 citations livelihood, religious system 30 quotes and quotations art 3. The implications of these results are the link between teaching literature in high school to teach about Babad Tanah Jawi. Because the Babad Tanah Jawi's story introduces us about the social and cultural contained in Java, as well as efforts in preserving classic literature.